Comparison of Black Soldier Fly (BSF) Maggot Nutrition with Different Culture Media - Nurhayati; Novita Sari; Said Muhazzir; Lia Handayani; Ismarica; Dolorosa, Maretty Twentyna; Pandang, Ivonda Vicana; Pradana, Hengki; Riandi, Muhammad (Yayasan Sagita Akademia Maju, 2024)
Maggot Black Soldier Fly (Hermetia illucens) is one of the natural feeds widely used by fish farmers. Maggot has a high nutritional content so that it is in great demand by the community. This study aims to determine the nutritional value contained in maggot cultured using different culture media. The culture media used in this study include fermentation of tofu waste and fermentation of fish waste. Fermentation of culture media was carried out for 7 days using EM4, sugar and water. The parameters analyzed in this study included protein content, fat content, water content, ash content and carbohydrates. The results showed that maggots cultured using fish waste fermentation culture media had a higher protein content compared to tofu waste fermentation culture media. The nutritional value of the fish waste fermentation treatment was 33.94% protein, 8.13% moisture content, 2.85% ash content, 3.31% fat and 51.16% carbohydrate.